HUBUNGAN KEMAMPUAN MANAJERIAL, MOTIVASI KERJA, DAN PERSEPSI PENGELOLA TERHADAP PROGRAM PEMBERDAYAAN DENGAN MUTU PELAYANAN PKBM DI KABUPATEN GARUT - Uum Suminar (Jurnal Ilmiah Visi, 2007)
The growth of Society Learning Activities Centre (PKBM) in quantity/amount, has not been balanced againts the quality improvement, especially in its services. One of factors influencing the quality of PKBM sevices is organizer resource factor. The target of this research is to lay open how far the relation of managerial ability, work motivation, and organizer perception to empowerment program with the quality of PKBM services. This research uses the quantitative approach. Problem focus analysis is conducted with the correlation descriptive analysis method, because this research is to lay open the relation of researched variables. Research population is 93 organizers of PKBM in Garut. Sampling technique used is simple random by proportional to 54 organizer people from 11 PKBM. Questionaire is used to collect the data. The conclusion of this research is there are significant relations between organizer managerial ability with the service quality, there are significant relations between motivation of work with the service quality, there are significant relations between organizer perception to empowerment program with the service quality, and there are significant relations between merger variables together with the service quality of PKBM.